The Influence Of Food And Beverage Product Marketing On Consumer Purchasing Interest (Case Study Of Eight-Mart & Canteen In Serang City) - Yoga Adiyanto (Brilliant International Journal Of Management And Tourism, 2023)
Marketing cannot be separated from the term marketing mix, which includes place, product, price and promotion. Eight Mart & Canteen is one of the Minimarkets & Canteens that implements this marketing mix strategy with the aim of attracting consumer buying interest so that these consumers can accelerate and improve the development of Minimarkets & Canteens and ultimately increase income turnover. This type of research is field research research ), which is quantitative correlational in nature, because it attempts to find out whether or not there is a causal relationship between the influence of the independent variable and the dependent variable. Data collection techniques in this research used interviews, distributing questionnaires and documentation. The interview technique used was unstructured interviews conducted with employees and managers of Eight Mart & Canteen. The questionnaire was distributed to 67 respondents using a Likert scale measurement. Meanwhile, documentation is used to complete research data to make it easier to study in depth. Documentation in the form of collecting brochures and menu lists at Eight Mart & Canteen. The research results show that the t test calculation shows that the t count is greater than the t table (2.597 > 2.000) so that the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. With the alternative hypothesis accepted, it can be said that the marketing variable (X) has a significant effect on consumer buying interest (Y). The marketing regression coefficient value (X) is 0.431. This shows that the regression coefficient is positive.